Ingkar Janji Menikahi sebagai Perbuatan Melawan Hukum: Kajian Putusan No. 18/PDT.G/2023/PN MGG - Ruth Nasya Mirachel Siregar; Zakki Adlhiyati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the legal status of marriage promises within the perspective of unlawful acts (PMH) according to the Indonesian civil law system, and to examine judicial considerations in determining legal liability and compensation in cases of marriage promise breaches in Decision Number 18/Pdt.G/2023/PN Mgg. This study employs a normative approach with a case study method. The findings demonstrate that breaking a marriage promise can be qualified as an unlawful act if it meets the elements of Article 1365 of the Civil Code (KUH Perdata), namely the presence of an unlawful act, fault, damages, and causality. In Decision Number 18/Pdt.G/2023/PN Mgg, the judge ruled that the breach of marriage promise resulting in material and immaterial losses can be sued as an unlawful act. The judge's considerations include analysis of evidence, causal relationships, and the impact of damages suffered by the plaintiff. This decision emphasizes the importance of legal protection for individuals harmed by marriage promise breaches.